Enhancing Students’ Critical Thinking Skills in Islamic Religious Education through Problem-Based Learning - Alfan Firmansyah; Irfan Afandi; Al Muftiyah (Al-Qalam Institue, 2026)
This study aims to analyze the implementation of Problem-Based Learning (PBL) in fostering students’ critical thinking skills in Islamic Religious Education. A descriptive qualitative approach was employed to explore the learning process and its influence on students’ critical thinking development. The participants consisted of two Islamic Religious Education teachers and three tenth-grade students selected through purposive sampling to represent high, moderate, and low levels of classroom participation. Data were collected through semi-structured interviews, two classroom observations, and document analysis. The data were analyzed using thematic analysis involving coding, categorization, and theme development, while credibility was ensured through source and method triangulation as well as member checking. The findings indicate that PBL was implemented through contextual problem presentation, collaborative group work, information investigation, class presentations, and reflective discussions. This learning model stimulated students’ ability to identify problems, justify arguments, consider multiple perspectives, and relate Islamic values to real-life situations. Nevertheless, improvements in critical thinking were not equally distributed, as some students still encountered difficulties in evaluating source credibility, constructing logical conclusions, and actively participating in discussions. The effectiveness of PBL was influenced by the quality of learning problems, teacher scaffolding, group role allocation, information literacy, and a supportive classroom environment. These findings imply that PBL should be implemented systematically, continuously, and adaptively to optimize students’ critical thinking skills in Islamic Religious Education.